The April 2010 Russo-Ukrainian gas agreement and its implications for Europe - Pirani, S; Yafimava, K; Stern, J (Oxford Institute for Energy Studies, 2010)
An agreement signed on 21 April 2010 by Russian president Dmitry Medvedev and his newly-elected Ukrainian counterpart Viktor Yanukovich provided for a 30% discount on Russian gas imported to Ukraine, in return for a 25-year extension of the lease to Russia of the Black Sea naval base at Sevastopol. The agreement came along with declarations from both sides that political and diplomatic relationships would improve after the departure of Yanukovich‟s predecessor Viktor Yushchenko, whose pronounced pro-western foreign policy, centred on NATO accession, was distrusted in Moscow. There followed a flurry of other proposals for deeper Russo-Ukrainian cooperation – in the electricity generation, atomic, aerospace and telecoms sectors, among others. This article considers the significance of the new agreement with Russia, (a) for Ukraine as a gas transit country, and for the European states that rely on Russian imports transported via Ukraine, and (b) for the Ukrainian gas market.